Synthesis, characterization, and adsorption performance of naphthalene-based covalent organic polymer for high-efficiency methylene blue removal - Omid Rahmanian; Mohammad Dinari; Nasim Mohammadi; Leila Aliakbarian (Scientific Reports)
Abstract In this study, a novel naphthalene-based covalent organic polymer (N-COP) was synthesized and investigated as an advanced adsorbent for the efficient removal of Methylene Blue (MB) from aqueous solutions. The polymer was synthesized through a polycondensation reaction between cyanuric chloride and 1,5-dihydroxynaphthalene, followed by thorough purification. Comprehensive characterization was performed using Fourier Transform Infrared (FT-IR) spectroscopy, X-Ray Diffraction (XRD), Thermogravimetric Analysis (TGA), Brunauer–Emmett–Teller (BET) surface area analysis, and Field Emission Scanning Electron Microscopy (FE-SEM), confirming the successful formation of the porous polymer with a high surface area and thermal stability. Key adsorption parameters including pH, contact time, and initial MB concentration were systematically optimized. The adsorption behavior followed the Langmuir isotherm model under conditions of pH 7 and a contact time of 30 min, indicating a maximum uptake capacity of 90.09 mg/g, while kinetic analysis revealed a strong fit with the pseudo-second-order model. These results demonstrate that N-COP is a promising candidate for environmental applications (in compression with other adsorbents), particularly in the removal of MB from wastewater, offering an eco-friendly, high-efficiency solution to mitigate water pollution.